The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.radonc.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Modelling duodenum radiotherapy toxicity using cohort dose-volume-histogram data

Abstract: Background and purposeGastro-intestinal toxicity is dose-limiting in abdominal radiotherapy and correlated with duodenum dose-volume parameters. We aimed to derive updated NTCP model parameters using published data and prospective radiotherapy quality-assured cohort data.Material and methodsA systematic search identified publications providing duodenum dose-volume histogram (DVH) statistics for clinical studies of conventionally-fractionated radiotherapy. Values for the Lyman-Kutcher-Burman (LKB) NTCP model we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Therefore, an accurate understanding of toxicity to normal tissue is critical. Significant efforts have been made in the development and validation of accurate normal tissue complication probability (NTCP) models, 6 , 7 , 8 , 9 which aim to characterize the correlation between dose and the likelihood of side effects. 10 Specifically, Lyman-Kutcher-Burman (LKB) NTCP models have been used to investigate the dose-volume response for liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an accurate understanding of toxicity to normal tissue is critical. Significant efforts have been made in the development and validation of accurate normal tissue complication probability (NTCP) models, 6 , 7 , 8 , 9 which aim to characterize the correlation between dose and the likelihood of side effects. 10 Specifically, Lyman-Kutcher-Burman (LKB) NTCP models have been used to investigate the dose-volume response for liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…'e e tl Shi oto et al ha e pu lished a al sis of carbon-ion chemoradiotherapy dose-volume parameters, though the values themselves may not be directly comparable with those from photon radiotherapy [28]. It is worth noting that in our analysis we failed to show associations of GI toxicity with duodenum dose-volume, despite other studies having shown evidence of a relationship [29]. Murphy et al showed a trend for association of increased duodenal dose-olu e ith g ade ≥ GI to i it i patie ts t eated ith o o ita t gemcitabine [7], but Huang et al found the best predictor of toxicity in similar patients was the duodenum V35Gy (V25Gy when including patients who received concomitant erlotinib) [9].…”
Section: Discussionmentioning
confidence: 60%
“…Where D is the total dose in Gy given in d Gy fractions of d = 2 Gy each using an r α/β ratio of 4. As published reports of late bowel toxicity have shown the appropriate α/β ratio is 3–5 [ 31 34 ].…”
Section: Methodsmentioning
confidence: 99%